2004
DOI: 10.1124/mol.65.3.802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SEA0400 on Mutant NCX1.1 Na+-Ca2+ Exchangers with Altered Ionic Regulation

Abstract: SEA0400 (SEA) blocks cardiac and neuronal Na ϩ -Ca 2ϩ exchange with the highest affinity of any known inhibitor, yet very little is known about its molecular mechanism of action. Previous data from our lab suggested that SEA stabilizes or modulates the transition of NCX1.1 exchangers into a Na ϩ i -dependent (I 1 ) inactive state. To test this hypothesis, we examined the effects of SEA on mutant exchangers with altered ionic regulatory properties. With mutants where Na ϩ i -dependent inactivation is absent, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
7
22
0
Order By: Relevance
“…These data suggest that the inhibitory effect of SN-6 is related to the kinetics of I 1 inactivation. Similar results have also been observed in other benzyloxyphenyl derivatives, including KB-R7943 and SEA0400 (Bouchard et al, 2004;Iwamoto et al, 2004). K229Q apparently works as a constitutively active exchanger, as do Y224W/Y226W/Y228W/ Y231W (termed XIP-4YW) and ⌬229-232, which were used in the above-cited reports.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These data suggest that the inhibitory effect of SN-6 is related to the kinetics of I 1 inactivation. Similar results have also been observed in other benzyloxyphenyl derivatives, including KB-R7943 and SEA0400 (Bouchard et al, 2004;Iwamoto et al, 2004). K229Q apparently works as a constitutively active exchanger, as do Y224W/Y226W/Y228W/ Y231W (termed XIP-4YW) and ⌬229-232, which were used in the above-cited reports.…”
Section: Discussionsupporting
confidence: 63%
“…This possibility received support from the evidence that benzyloxyphenyl derivatives had hypersensitivities to N1-F223E, which are able to very quickly enter an I 1 inactive state (Bouchard et al, 2004;Iwamoto et al, 2004). Therefore, we speculate that the interaction of benzyloxyphenyl derivatives with the exchanger probably stabilizes the I 1 inactive state or accelerates the rate of entry into an I 1 inactive state.…”
Section: Ncx Inhibition By Sn-6 53mentioning
confidence: 58%
“…Furthermore, we evaluated the effects of YM-244769 on NCX1 mutant (i.e., D447V/D498I) displaying a phenotype for a low regulatory Ca 2ϩ affinity, but we could not detect a significant relationship between the drug sensitivity and I 2 inactivation. These properties have also been observed in other benzyloxyphenyl derivatives (Bouchard et al, 2004;Iwamoto et al, 2004a,b).…”
Section: Neuroprotection By Ym-244769 2081supporting
confidence: 50%
“…In existing benzyloxyphenyl NCX inhibitors, reverse mode-selectivity is commonly observed under unidirectional ionic conditions (Iwamoto et al, 1996(Iwamoto et al, , 2004aWatano et al, 1996;Bouchard et al, 2004). On the other hand, other data have shown that both SEA0400 and KB-R7943 equally block outward and inward exchange cur- , and NCX3 isoforms in SH-SY5Y and LLC-PK 1 cells, microsomes (30 g) from cells or from mouse brain were subjected to immunoblot analyses with specific antibodies against the isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the major inhibitory effects of SEA0400 require the presence of intracellular Na ϩ and generally follow the preponderance of the I 1 inactive state. Similar conclusions have been reached based on the evaluation of mutant Na ϩ -Ca 2ϩ exchangers with altered I 1 inactivation (Bouchard et al, 2004;Iwamoto et al, 2004).…”
supporting
confidence: 62%